In-beam γ-spectroscopy with relativistic radioactive ion beams - Wan, Scott; Gerl, J.; Cub, J.; Holeczek, J.M.; Reiter, P.; Schwalm, Dirk; Aumann, T.; Boretzky, K.; Dostal, W.; Eberlein, B.; Emling, H.; Ender, Ch.; et al. (The European physical journal. A, Hadrons and nuclei, 1999)
This work demonstrates the feasibility of in-beam γ-spectroscopy employing radioactive ion beam species at relativistic energies of E = 210 ∼ 280 A· MeV. Neutron-rich nuclei below 48Ca with neutron number between the two magic numbers 20 and 28 have been investigated. Using a Pb target, single step inelastic excitation originating mainly from Coulomb interaction takes place populating preferentially low-lying low-spin states and enabling the extraction of B(E2) values. On a C target, nucleon removal reactions are dominating and medium-spin states are populated thus offering spectroscopic information in neighboring nuclei. Cross sections of inelastic excitation are determined and compared to coupled-channels calculations. Two new states of the very neutron-rich nucleus 44Ar at 1.78(8) MeV and 2.61(16) MeV are deduced from γ-transitions.
Gesehen am 26.11.2020